Official promotion and extreme environmental regulation: Evidence from prefecture-level cities in China - Meng, Zuhan; Shi, Anna; Du, Sixuan (Frontiers in Public Health, 2022)
Under the background of Chinese decentralization, avoiding the shortsightedness of local officials has become the policy focus of the central government's environmental regulation. In recent years, with the achievement of environmental protection gradually becoming a necessity for promotion, local officials increasingly prefer to implement extreme environmental regulation (EER) to quickly control environmental deterioration. Based on this specific fact, this paper constructs a systematic GMM model, trying to study whether the promotion of officials can fully explain the executive logic of EER under the influence of limited tenure and geographical rotation. It is found that EER and limited tenure have a U-shaped relationship, and geographical rotation can inhibit EER during the limited tenure. In addition, China has not formed an “environment-only” promotion tournament. Heterogeneity analysis showed that in areas with high bureaucratic compliance, local officials are late in strengthening EER during their tenure while the inhibition effect of geographical rotation is poor; Compared with older officials, young officials have stronger motivation to implement EER, and the inhibition of geographical rotation is obvious. To sum up, our research shows that the green promotion system only enhances officials' demands for environmental achievements, but it does not restrict officials' short-sighted governance strategies. The central government should start by expanding environmental protection assessment indicators and improving the quality of official rotation to narrow the implementation space of EER, thereby encouraging local governments to promote stable and sound environmental governance in a compliant and long-term manner.